The Effect of Mudharabah, Musyarakah, Murabahah Finance on Return on Asset (ROA) - A'yuni, Diah Syifaul; Fauziah, Nur Dinah; Purwanto, Purwanto (Majapahit Journal of Islamic Finance and Management, 2021)
Bank is a financial institution whose main activity is to collect funds from the public and then distribute these funds back to the community. The purpose of this study was to determine the effect of Mudharabah, Musyarakah, Murabahah financing on Return on Assets (ROA) at Bank Syariah Mandiri for the 2009-2018 period. The dependent variable of this research is Return on Assets. The independent variables include: financing, Mudharabah, Musyarakah and Murabahah. The research method used is a quantitative research method. The data analysis method used multiple linear regression. The results of the study indicate that Mudharabah financing has an effect on Return on Assets (ROA) with a significant level of 0.000 <0.05. Musyarakah financing has an effect on Return on Assets (ROA) with a significant level of 0.010 <0.05. Murabahah financing has no effect on Return on Assets (ROA) with a significant level of 0.210> 0.05. Mudharabah, Musyarakah, Murabahah financing together can influence the dependent variable with a significant value of 0.000> 0.05.